2010
DOI: 10.1080/10615800903191137
|View full text |Cite
|
Sign up to set email alerts
|

Does narrative writing instruction enhance the benefits of expressive writing?

Abstract: We examined whether instructing participants to write in a narrative fashion about stressful life events would produce superior physical and psychological health benefits relative to standard expressive writing instructions that do not specify the essay's structure. Undergraduates (N = 101) were randomly assigned to engage in two, 20-minute narrative writing, standard expressive writing, or control writing tasks. Follow-up data were obtained one month later. The essays of the narrative writing group evidenced … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
16
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 32 publications
(19 citation statements)
references
References 46 publications
2
16
0
1
Order By: Relevance
“…We did not receive any comments from newcomers that the survey was too diffi cult; rather, spontaneous comments were uniformly positive (e.g., "Thank you for this study that allows me to get it all out of my system," "Thank you for the opportunity to let me share a little of my story."). These results agree with prior studies (Baddeley and Pennebaker, 2011;Danoff-Burg et al, 2010) showing that distressed participants may perceive benefi ts from sharing their experiences, often in the hope of helping other people with similar struggles.…”
Section: Methodssupporting
confidence: 83%
“…We did not receive any comments from newcomers that the survey was too diffi cult; rather, spontaneous comments were uniformly positive (e.g., "Thank you for this study that allows me to get it all out of my system," "Thank you for the opportunity to let me share a little of my story."). These results agree with prior studies (Baddeley and Pennebaker, 2011;Danoff-Burg et al, 2010) showing that distressed participants may perceive benefi ts from sharing their experiences, often in the hope of helping other people with similar struggles.…”
Section: Methodssupporting
confidence: 83%
“…These results are consistent with other accounts of EW in which the narrative elements of the intervention were important for recovery following trauma and social disruption when using EW (27-30). Undergraduate students who were asked to engage in traditional EW, narrative EW or a control writing task and had higher levels of narrative structure, for example, yielded positive gains in terms of their psychological wellbeing (41). …”
Section: Discussionmentioning
confidence: 99%
“…Others have also reported that instructional narrative writing helps writers to secure their mental health (Danoff-Burg, Mosher, Seawell, & Agee, 2010). Danoff-Burg et al (2010) stated that traumatic memories can be alleviated through sharing stories because patients can simplify their terrible memories, which are not restored "as sensory perceptions, obsessional ruminations, or behavioral reenactments, as in the case of posttraumatic stress disorder" (p. 342). Such a discussion in previous research sheds light on the importance of a narrative writing task for L2 writers who may be marginalized in a target language community (Burke, 2010).…”
Section: Resultsmentioning
confidence: 99%